Feasibility of microalgae as feedstock for alternative fuel in Malaysia: A review - Hossain N.; Hasan M.H.; Mahlia T.M.I.; Shamsuddin A.H.; Silitonga A.S. (Elsevier Ltd, 2023)
Algae; Crude oil price; Economics; Energy security; Feedstocks; Growth rate; Microorganisms; Palm oil; Petroleum prospecting; Biodiesel production; Biomass productivity; Commercial transportation; Environmental conditions; Geographical locations; Microalgae cultivation; Microalgae harvesting; Potential feedstock; Biodiesel